Norm power of scuba diving and snorkeling behaviors in the Florida Keys. (1st September 2022) - Allen, Mary E.; Loomis, David K.; Vaske, Jerry J.
Abstract: The sustainability of recreation and tourism in coral reefs depends on ecological health and environmentally responsible behaviors in those ecosystems, which are partly guided by social norms. The power of social norms lies in the behavioral obligations imposed by a group, and in the informal sanctions enforced by others or felt by oneself when conforming to or violating those obligations. This study examined the norm power of 12 coral reef behaviors of non-resident SCUBA divers and snorkelers in the Florida Keys. In a mail questionnaire, respondents rated how obligated they were to do each of the 12 behaviors when diving or snorkeling on a coral reef, and how embarrassed (informal sanction) they would feel if they were seen violating each of those behaviors. Overall, the results showed that divers and snorkelers were obligated to do all 12 types of behaviors, but the amount of norm power was distinguished by the level of embarrassment varying between the two groups. High norm power values suggest that SCUBA divers and snorkelers self-regulate and enforce desirable behaviors within their activity groups. Relatively low norm power behaviors should be monitored and may need targeted communication strategies or management interventions to help instill a sense of obligation and sanction. These findings have important implications for monitoring behavioral compliance, promoting ocean stewardship, and establishing management policies to sustain coral reef ecosystem services. Highlights: SCUBA divers and snorkelers have normative standards for behavior in coral reefs. The power of social norms for behavior is a function of obligations and sanctions. High norm power suggests behaviors are self-regulated and enforced within a group. Low norm power behaviors may need monitoring, formal sanctions or interventions. Norm power results inform management on compliance, stewardship, and outreach.